KPC pancreatic cancer cells are a novel immunocompetent murine model supporting human adenovirus replication and tumor oncolysis - Marc Otero-Mateo; Francesc Estrany Jr; Sabrina Arcas-Márquez; Laura Moya-Borrego; Giancarlo Castellano; Miquel Castany; Ramon Alemany; Cristina Fillat (Molecular Therapy: Oncology)
Oncolytic adenoviral therapy is a promising approach for pancreatic cancer treatment. However, the limited capacity of murine cells to produce infectious viral progeny precludes the full evaluation of the virotherapy in a suitable immunocompetent mouse model. Here, we report that the murine KPC-I cell line, established from pancreatic tumors developed in LSL-KrasG12D; LSL-Trp53R172H; Pdx-Cre mice, is susceptible to adenoviral replication and generates a progeny of infective virions similar to those from infected human A549 cells. A comparative study with the semipermissive murine CMT64.6 cells reveals that adenoviral infection of KPC-I cells substantially increases the release of infective particles, with a correlating enhanced susceptibility to adenovirus-induced autophagy. Remarkably, systemic delivery of the oncolytic adenovirus AdNuPARE1A in athymic mice bearing KPC-I tumors results in significant inhibition of tumor growth. Moreover, KPC-I tumors in immunocompetent mice with intratumoral administration of AdNuPARE1A or ICOVIR15kDelE3 display significant antitumoral effects, with evidence of adenoviral replication. Collectively, our data show that KPC-I cells are permissive to human oncolytic adenovirus replication, rendering KPC-I syngeneic tumors an interesting model to evaluate the multifaceted antitumor activities of oncolytic adenovirus.